(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
The article examines the term as a necessary tool for professional thinking, professional mastery of objective reality, the most important tool for scientific communication and the problem of isolating a term from a text. Terms, or rather, their application and use by people, can be (and often are) the cause of partial, or even complete, mutual misunderstanding among scientists in the process of cognition and communication. The polysemy of a term not removed by the context, the hidden substitution of one meaning of a term for another, the vagueness of the conceptual boundaries of a term, the actual non-terminality of words functioning as a term - all these are quite common “terminological situations” of modern science, which certainly complicate scientific communication and reduce its effectiveness. That is why perhaps the most important task of terminology at the present stage can be considered to clarify the subject and conceptual relevance of basic terms in every science, including linguistics. It is necessary to clearly understand that the substantive relevance of a term arises due to its denotative connection with the reality it denotes (denotation), and it is impossible to successfully use a term if its substantive relevance is vague or multidirectional, i.e. it is unclear what phenomenon of reality, which aspects of it are designated one term or another. But the term not only denotes a certain reality, but also expresses and forms a scientific concept about it. The significative connection of a term, i.e. its connection with a scientific concept, determines its conceptual relevance.